Pengaruh Keamanan, Kemudahan Bertransaksi, Kepercayaan Konsumen Terhadap Minat Beli Konsumen Pada E Commerce Shopee (Studi Kasus Pada Pengguna Aplikasi Shopee Di Jakarta Utara) - Nabila Nabila; Muhamad Sholeh (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine how much influence Security, ease of transaction, and consumer confidence on consumer buying interest in Shopee E Commerce (case study on Shopee application users in North Jakarta). The research method used is quantitative method. Data acquisition was done through the distribution of questionnaires using Google form to 140 respondents with purposive sampling technique. The results of this study showed that the results of the determinant coefficient R square which shows that: 1) Security has a positive and significant effect on buying interest. 2) ease of transaction has a positive and significant influence on buying interest. 3) Consumer Confidence has a positive and significant influence on buying interest.